Analysis of PPATK's Authority in Blocking Dormant Accounts Indicated by Criminal Offenses: Perspectives of Due Process of Law and Legal Certainty - Paizal Reza; Padlilah; Bram B. Baan (Fakultas Syariah INSURI Ponorogo, 2026)
This article analyzes the authority of the Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK) in requesting the temporary suspension of transactions on dormant accounts linked to money laundering. It examines how PPATK's administrative-intelligence authority operates within criminal law when dormant status, originally an administrative category, becomes associated with criminal suspicion. Using normative juridical research with statutory and conceptual approaches, this study examines Law No. 8 of 2010, PPATK Regulation No. 18 of 2017, POJK No. 24 of 2025, criminal doctrine, due process of law, and legal certainty. The findings show that a temporary suspension creates problems when account dormancy is treated as a criminal indicator without specific parameters for suspicion. Such practice may produce a presumption of suspicion and blur the boundary between financial intelligence, investigation, and judicial proof. It argues that PPATK is a preventive actor whose authority must be governed by legality, proportionality, the presumption of innocence, due process, and Dignified Justice.